Nematódeos e bactérias em fôlhas de alcachôfra - Lordello, Luiz Gonzaga E.; Joly, S.; Campos, Humberto Ribeiro de; Camargo, Leocádio de Souza (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1961)
Diseased plants of artichoke (Cynara scolimus L.) from the Instituto Agronômico, Campinas, Brazil, harboured nematodes in the leaves. The nematodes proved to belong to the species Protorhabditis oxyuris (Claus, 1862) Dougherty, 1955. As it could not be charged as the primary agent of the disease, a study of the bacteria found in the material was made. This disclosed that 4 different bacterial forms were present, namely Bacillus subtilis, Bacterium udum, Xanthomonas beticola var. cynarae n. var., and Cory neb acterium fascians var. cynarae n. var. The typical forms of X. beticola and of C. fascians are known as pathogenic to a number of plants: but, in the present case, unfortunately no inoculation trial could be made as an attempt to clear up the possible pathogenicity of any of them also to Cynara scolimus. The nematode P. oxyuris is the secondary agent, which however possibly play an important part in the distribution of the bacteria, as it has been repeatedly pointed out by previous writers with reference to closely related species. The symptoms of the disease are described. The main injuries found on leaves were necrotic areas progressing from the distal part of the limb, resulting in a great reduction of the leaf superficies.